INI1/SMARCB1 Rpt1 domain mimics TAR RNA in binding to integrase to facilitate HIV-1 replication - Updesh Dixit; Savita Bhutoria; Xuhong Wu; Liming Qiu; Menachem Spira; Sheeba Mathew; Richard Harris; Lucas J. Adams; Sean Cahill; Rajiv Pathak; P. Rajesh Kumar; Minh Nguyen; et al. (Nature Communications, 2021)
HIV-1 integrase (IN) binds the host factor INI1/SMARCB1, which is required at multiple stages of HIV-1 replication. Here, the authors show that the same IN residues are involved in INI1 and RNA binding and in influencing particle morphogenesis and suggest that the IN-binding INI1 domain is structurally similar to HIV TAR RNA.